Long open-path measurements of greenhouse gases in air using near-infrared Fourier transform spectroscopy - Griffith, David W. T.; Pöhler, Denis; Hammer, Samuel; Vardag, Sanam Noreen; Platt, Ulrich; Schmitt, Stefan (Atmospheric measurement techniques, 2018)
In complex and urban environments, atmospheric trace gas composition is highly variable in time and space. Point measurement techniques for trace gases with in situ instruments are well established and accurate, but do not provide spatial averaging to compare against developing high-resolution atmospheric models of composition and meteorology with resolutions of the order of a kilometre. Open-path measurement techniques provide path average concentrations and spatial averaging which, if sufficiently accurate, may be better suited to assessment and interpretation with such models. Open-path Fourier transform spectroscopy (FTS) in the mid-infrared region, and differential optical absorption spectroscopy (DOAS) in the UV and visible, have been used for many years for open-path spectroscopic measurements of selected species in both clean air and in polluted environments. Near infrared instrumentation allows measurements over longer paths than mid-infrared FTS for species such as greenhouse gases which are not easily accessible to DOAS. In this pilot study we present the first open-path near-infrared (4000-10000 cm−1, 1.0-2.5 µm) FTS measurements of CO2, CH4, O2, H2O and HDO over a 1.5 km path in urban Heidelberg, Germany. We describe the construction of the open-path FTS system, the analysis of the collected spectra, several measures of precision and accuracy of the measurements, and the results a four-month trial measurement period in July-November 2014. The open-path measurements are compared to calibrated in situ measurements made at one end of the open path. We observe significant differences of the order of a few ppm for CO2 and a few tens of ppb for CH4 between the open-path and point measurements which are 2 to 4 times the measurement repeatability, but we cannot unequivocally assign the differences to specific local sources or sinks. We conclude that open-path FTS may provide a valuable new tool for investigations of atmospheric trace gas composition in complex, small-scale environments such as cities.